Roles of traditional chinese medicine regulating neuroendocrinology on AD treatment - Deng, Chujun; Chen, Huize; Meng, Zeyu; Meng, Shengxi (Frontiers in Endocrinology, 2022)
The incidence of sporadic Alzheimer's disease (AD) is increasing in recent years. Studies have shown that in addition to some genetic abnormalities, the majority of AD patients has a history of long-term exposure to risk factors. Neuroendocrine related risk factors have been proved to be strongly associated with AD. Long-term hormone disorder can have a direct detrimental effect on the brain by producing an AD-like pathology and result in cognitive decline by impairing neuronal metabolism, plasticity and survival.Traditional Chinese Medicine(TCM) may regulate the complex process of endocrine disorders, and improve metabolic abnormalities, as well as the resulting neuroinflammation and oxidative damage through a variety of pathways. TCM has unique therapeutic advantages in treating early intervention of AD-related neuroendocrine disorders and preventing cognitive decline. This paper reviewed the relationship between neuroendocrine and AD as well as the related TCM treatment and its mechanism. The advantages of TCM intervention on endocrine disorders and some pending problems was also discussed,and new insights for TCM treatment of dementia in the future was provided.